Surgical management of primary and idiopathic internal hydrocephalus in dogs and cats - Schmidt, Martin J.; Farke, Daniela (Frontiers in Veterinary Science, 2024)
Ventriculoperitoneal shunt placement is an effective method to treat internal hydrocephalus in dogs and cats. Although it has a long history in veterinary medicine, the technique continues to evolve. Despite continuing attempts to reduce the incidence of associated complications, shunt failure remains a major problem, and often leads to multiple hospital admissions. This review gives an overview about current knowledge of ventriculoperitoneal shunting techniques in animals, applicable shunt hardware as well as shunt-associated complications and their prevention and treatment.